Uji Kinerja Burner dan Tabung Reaktor Flame Untuk Proses Spray Pyrolysis - Darmawan Hidayat; Ganjar Nurohman; S Setianto; Bambang Mukti Wibawa; Nendi Suhendi (Dept. of Chemical Engineering, Diponegoro University, 2017)
Abstract PERFORMANCE EVALUATION OF BURNER AND THE REACTOR TUBE OF FLAME FOR A SPRAY PYROLYSIS PROCESS. Flame spray pyrolysis is a versatile process in the syntheses of various functional materials. This work reports the performance of a diffusion flame built from a coaxial burner and a Pyrex-glass tube reactor with respect to the relatively low propane flow rates (0.1-0.8 L/min). The burner comprised of three cylindrically tubes with three inlets for fuel (propane), oxidant (oxygen) and precursor aerosol. Three flame parameters were measured, i.e. the flame height, flame temperature and reactor temperature profile, respectively. The test results showed the increase of the flame height and temperature with increasing of propane flow rate. The temperature profile measurements showed the decreasing as the height above burner increased; and temperature profile increased at the increasing propane flow rate. The reactor temperature was in the range of 36-190°C at low propane flow rates of 0.1-0.8 L/min. In conclusion, control of flame process parameters could be conducted by controlling of propane flow rate. Keywords: diffusion flame burner; spray pyrolysis; flame reactor; electronic material syntheses Abstrak Pirolisis flame spray merupakan proses yang banyak digunakan untuk keperluan sintesis bahan-bahan fungsional. Makalah ini melaporkan kinerja sebuah reaktor flame difusi yang dibangun dari sebuah pembakar (burner) dan tabung reaktor silinder. Pembakar dibangun dari tiga buah silinder stainless steel yang dipasang koaksial sebagai saluran bahan bakar propana, oksidator oksigen dan aerosol prekursor. Tiga parameter proses flame yang diuji adalah tinggi flame, temperatur flame dan profil temperatur tabung reaktor. Hasil pengujian menunjukkan bahwa seiring kenaikan laju alir propana, tinggi dan temperatur flame meningkat. Pengukuran profil temperatur menunjukkan penurunan seiring kenaikan posisi dari ujung-atas pembakar; dan temperatur profil reaktor meningkat seiring dengan kenaikan laju alir propana. Temperatur reaktor berkisar 36-190°C pada laju alir propana rendah 0,1-0,8 L/min. Dapat disimpulkan bahwa pengontrolan parameter-parameter proses flame dapat dilakukan dengan pengaturan laju alir propana. Kata kunci: diffusion flame burner; proses spray pyrolysis; reaktor flame; sintesis bahan elektronik